Visual-spatial functioning as an early indicator of socioemotional difficulties - Tonks, James; Yates, Phil; Slater, Alan; Williams, W. Huw; Frampton, Ian (Developmental neurorehabilitation, 2009)
Primary objective: As children with acquired brain injuries (ABI) mature to become adolescents they develop a range of previously undetected social and emotional difficulties, which are commonly associated with executive dysfunctions. The authors wanted to determine whether visual-spatial performance is subject to age-related improvement, whether such skills can differentiate between children with ABI and healthy children and whether visual-spatial performance is a correlate of socioemotional functioning. Research design: The 'Cube analysis' and 'Dot discrimination' tests from the 'Visual Object Space Perception (VOSP)' battery and the Strengths and Difficulties Questionnaire (SDQ) were administered for 18 children, 9-15 years, with ABI and compared against 67 'healthy' children. Results: Cube analysis scores improved significantly at ∼10 years old in the control group. The ABI group performed the task significantly poorer than controls. Analysis indicated that visual discrimination skill did not account for performance difficulties. Visual-spatial performance was correlated with greater impact of reported difficulties on the SDQ. Conclusions: Visual-spatial tests are sensitive in differentiating between healthy children and children with ABI. Impairment of visuo-spatial skills may provide an index of psychosocial risk during later teenage years and adulthood.